2017
DOI: 10.1017/s1047951117000944
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac autonomic function using heart rate variability in children with acute carbon monoxide poisoning

Abstract: The frequency domain indices, especially the ratio of low-frequency spectral power to high-frequency spectral power, are useful for the evaluation of the cardiac autonomic function. The decreased low-frequency spectral power-to-high-frequency spectral power ratio reflects a balance of the autonomic nervous system, which shifted to parasympathetic components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In these cases, the levels of LF/HF declined with the increase in the CO concentration. These results are consistent with the studies showing a decline in the levels of LF/HF with exposure to acute CO concentrations [23]. In a previous study, showed that, while an increase in the concentrations of dust contributes to increased levels of LF/HF, an increase in CO levels caused a decrease in the levels of LF/HF [24].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…In these cases, the levels of LF/HF declined with the increase in the CO concentration. These results are consistent with the studies showing a decline in the levels of LF/HF with exposure to acute CO concentrations [23]. In a previous study, showed that, while an increase in the concentrations of dust contributes to increased levels of LF/HF, an increase in CO levels caused a decrease in the levels of LF/HF [24].…”
Section: Introductionsupporting
confidence: 92%
“…These intervening factors may possibly reverse the negative relationship between low concentrations of CO and LF/HF. In other words, while an increase in CO concentration is associated with decreased LF/HF, other air pollutants and noise may increase the LF/HF ratio, as demonstrated in a recent study by Tang et al [23]. However, despite the dominant effect of NO 2 , this study aims to highlight the uniqueness of the behavior of CO.…”
mentioning
confidence: 83%
“…The record of electrocardiograms ranged from 5 min, 7 min, 15 min, 16 min, 30 min, 35 min, and 36 min to 24 h (ambulatory) in our included studies. However, a 5-min recording of electrocardiograms is recommended as longer recordings may be affected by emotions or physical activity [ 53 ]. The 24 h mean O 3 concentration was the most commonly used; however, there were studies with O 3 exposure periods of 1 h, 2 h, 4 h, 12 h, 24 h, 72 h and 120 h. Various mean period of O 3 concentrations and ECG recording lengths do not produce the same effect estimates on HRV indicators, which may also explain the heterogeneity observed in the associations of O 3 exposure with RMMSD, LF, and HF [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the case reports, the scarce literature on the acute effects of individual constituents of cigarette smoking on human in vivo ECG has mainly investigated nicotine and carbon monoxide. Acute carbon monoxide intoxication in children impaired ventricular repolarization with higher mean heart rate, QT dispersion, QTc dispersion, P dispersion, Tp-Te, QTc durations, Tp-Te dispersion, and Tp-Te/QT ratio compared to controls [230,231]. However, it increased heart rate, ST-T wave changes, QTc dispersion, and TpTe dispersion in adults [232,233].…”
Section: Acute Exposure To Smoking (Nicotine and Non-nicotine Constitmentioning
confidence: 96%